Características morfologicas de judocas do sexo feminino de diferentes categorias - Elipkhanov, S.; Nemtsev, O. (Revista Brasileira de Cineantropometria e Desempenho Humano, 2013)
The evaluation of morphological differences among female judoka of different grades would make it possible to estimate the influence of motor activity in judo on athletes` performances, leading to a more refined selection process in this sport. Therefore, this study aimed to compare the morphological characteristics of female judoka of different ranks. Twenty-three athletes of higher grades and thirty-two judoka of lower ranks participated in this study. We measured the lengths of six body segments and thecircumferences of twelve body segments, as well as nine skinfolds. We also evaluated body fat percentage. The mean differences between both groups were measured using ANOVA. This study shows that highly skilled judoka have significantly lower total body fat percentage (19.6 ± 4.4 and 22.7 ± 5.2 %, p < 0.05) and skinfold values (p < 0.05-0.01) in five body sites. They have significantly larger neck (34.4 ± 2.9 and 32.3 ± 2.4 cm, p < 0.01), thorax at forced inspiration (94.7 ± 5.1 and 91.4 ± 4.1 cm, p < 0.05) and expiration (88.6 ± 5.1 and 85.5 ± 4.4 cm, p < 0.05), and relaxed arm (27.8 ± 2.5 and 26.3 ± 2.1 cm, p < 0.05) circumferences. High-rank judoka have significantly longer hands (19.4 ± 1.3 and 18.1 ± 1.5 cm, p < 0.001) and significantly shorter thighs (37.2 ± 2.6 and 40.2 ± 3.2 cm, p < 0.001). Judoka with less body fat, more thoracic muscle mass, and shorter arms and legs are more successful in female judo.